2021
DOI: 10.3389/fcimb.2021.735191
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Administration of Recombinant Baculovirus Displaying Toxoplasma gondii ROP4 Confers Protection Against T. gondii Challenge Infection in Mice

Abstract: Pathogens require physical contact with the mucosal surface of the host organism to initiate infection and as such, vaccines eliciting both mucosal and systemic immune responses would be promising. Studies involving the use of recombinant baculoviruses (rBVs) as mucosal vaccines are severely lacking despite their inherently safe nature, especially against pathogens of global importance such as Toxoplasma gondii. Here, we generated rBVs displaying T. gondii rhoptry protein 4 (ROP4) and evaluated their protectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…Most of the immunological findings reported here are similar to the protective efficacy induced by ROP4-rBV vaccines as described in our previous study, although several differences in immunological parameters were noted [10]. Consistent with our previous study, a remarkable increase in GC B cells was observed from both the spleens and MLNs of mice.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Most of the immunological findings reported here are similar to the protective efficacy induced by ROP4-rBV vaccines as described in our previous study, although several differences in immunological parameters were noted [10]. Consistent with our previous study, a remarkable increase in GC B cells was observed from both the spleens and MLNs of mice.…”
Section: Discussionsupporting
confidence: 92%
“…Samples were collected as previously described [10]. Four weeks after each immunization, blood samples of mice were collected by retro-orbital plexus puncture.…”
Section: Sample Collection and Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, only a few studies investigated the potential of baculovirus-based vaccines against T. gondii [ 9 , 10 ]. Previously, we have also demonstrated that immunizing mice with the recombinant baculovirus (rBV) vaccines expressing the rhoptry protein 4 (ROP4) of T. gondii can induce protection [ 11 ]. Nonetheless, ROP4-rBV immunizations neither completely inhibited cyst formation nor prevented bodyweight loss following T. gondii ME49 challenge infection, which signified the need for further improvements.…”
Section: Introductionmentioning
confidence: 99%